Polypeptide involved in the Escherichia coli plasmid-mediated citrate transport system. - Hirato, T (1984)
A genetic determinant conferring on Escherichia coli the ability to utilize citrate as a sole source of carbon and energy was subcloned into pBR322 from a naturally occurring, citrate utilization (Cit+) plasmid, pOH30221, and was localized to a 1.6-kilobase region by cloning and subsequent deletion analysis. Genetic expression of the Cit+ determinant in E. coli minicells revealed that the Cit+ determinant encoded a single, membrane-associated polypeptide with an apparent molecular weight of 35,000, as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. This polypeptide seemed not to be synthesized as a precursor with an amino-terminal signal sequence.